Pengaruh Permainan Outbound Mystique Ball Terhadap Tingkat Kebugaran Jasmani Siswa (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2016)
The purpose of this study was to determine the effect of outbound mystique ball game on thelevel of physical fitness class VIII SMP Negeri 1 Kesesi Pekalongan in 2016. The research isa field experiment using praeksperimen design with one group pretest-postest design. The populationin this study is a class VIII student who numbered 254 students, this sample is classVIII E of the 36 students who carried out the random technique. The research instrumentused test Physical Freshness Indonesia (TKJI) for children aged 13-15 years. Analysis of thedata used is descriptive statistics percentages. The results of the study there were six students(16.67%) including the classification of Good, 16 students (44.43%) including classificationMedium, 10 students (27.77%) including the classification of Less, 4 students (11.11%) includedClassification Less Once. The conclusion of this study is the mystique outbound gameball effect so that the level of physical fitness class VIII SMP 1 Kesesi Pekalongan Year 2016Classification Medium. Based on the results of the discussion, the level of physical fitness ofstudents are influenced by factors such as physiology, the acquisition value of each test, as wellas the obstacles and weaknesses in the study.